Troubles with the CHF loans in Croatia: The story of a case still waiting to be closed - Ana Kundid Novokmet (Journal of Risk and Financial Management, 2021)
In numerous Central and Eastern European (CEE) countries, the global financial crisis as well as the unpegging of the foreign exchange rate of the Swiss franc (CHF) against the euro amplified the repayment troubles of households with the outstanding CHF-linked debt. In Croatia, the CHF loans were approved mainly as mortgages to unprotected and subprime household borrowers without sufficient credit capacity for long-term euro-linked loans, which also contained a possibility of an incremental interest rate change, i.e., the so-called administrative interest rate. This article aims to disclose the reasons behind the credit boom of these loans, the unsustainable CHF debt hardship that the household sector consequently faced, and how it was/could have been resolved, with the Croatian banking sector at the center of the research. Although the CHF case of Croatia has some specificities concerning the prudential regulation and government-sponsored loan conversion, the findings about the supply and demand determinants of the CHF credit boom, as well as a critical assessment of the Croatian government and central bank interventions, might be useful for timely noticing universal threats from the exotic currency-linked loans for the systemic risk and financial stability, and for minimizing the negative externalities from probable debt relief measures. Based on the descriptive and univariate statistics conducted on Bloomberg and the Croatian National Bank (CNB) data, it was found that interest rate differentials and carry trading behavior were the main reasons for the rapid CHF credit growth in Croatia. Nevertheless, according to the financial experts' opinions obtained via a questionnaire survey, and the court verdicts reached since, the financial consumer protection when contracting these loans was severely violated, which implies that the central bank must enhance its consumer protection role. By adopting a single-country and holistic approach, this is the first paper that deals with the socioeconomic dynamic of the CHF credit default issues in Croatia, which might be interesting as a case study or for making comparison with other CEE countries that have been coping with negative consequences of Swiss francization.
Keywords: 330; bank risk management; Croatian banking sector; debt crisis; financial consumer protection; foreign currency loans; foreign currency-induced credit risk; prudential regulation; questionnaire; retail banking; Swiss franc controversy